Ultrasonic and hypersonic investigations of vibrational relaxation in liquid thiophene - MIECZNIK, Piotr (Archives of Acoustics, 1978)
The measurements of hypersonic wave propagation velocity in the frequency range 2-7 GHz and ultrasonic wave absorption coefficient in the frequency range 10-60 MHz in thiophene have revealed the existence of two relaxation regions associated with vibrational specific heat: the first one associated with the first mode (v_1) of molecule vibrations and the second, associated with the remaining modes excluding the first one. It follows from the experimental values of hypersonic wave absorption coefficient that the bulk viscosity coefficient in this frequency range n_y,∞ exceeds by a factor 2.5 the laminar viscosity coefficient n_s.